Vital-sign data fusion models for post-operative patients - Pimentel, M; Clifton, D; Clifton, L; Watkinson, P; Tarassenko, L (ScitePress Digital Library, 2012)
Deterioration in Patients who undergo upper-gastrointestinal surgery may be evident in the vital signs prior to adverse events. A dataset comprising observational vital-sign data from 128 post-operative patients was used to explore the trajectory of patients vital-sign changes during their stay in the post-operative ward. A model of normality based on pre-discharge data from patients who had a "normal" recovery was constructed using kernel density estimates, and tested with "abnormal" data from patients who deteriorate sufficiently to be re-admitted to the Intensive Care Unit. The results suggest that the criticality of post-operative patients can be evaluated by assessment of the distributions of their vital signs after their admission to the post-operative ward.